A nuclear DNA helicase from pea (Pisum sativum L.) that translocates in the 3' to 5' direction - Hoi, Pham Xuan; Ham, Le Huy; Tuteja, Narendra (Academia Journal of Biology, 2014)
Transient opening of the stable duplex DNA is an essential prerequisite step in many biological processes such as DNA replication, repair, recombination and transcription. DNA helicases catalyses the unwinding of energetically stable duplex DNA (DNA helicase) or inter - and intramolecular base -paired duplex RNA (RNA helicase) structures by disrupting the hydrogen bonds between the two strands and thereby plays an important role in all aspects of nucleic acid metabolisms [5, 6, 8]. Gene pdh45, the first plant DNA helicase has been cloned, over-expressed and characterized in detail [5, 6]. In this article, the polyclonal antibodies directed against PDH45 were used to check the presence of PDH45 in purified pea nuclei, cytosol and chloroplast by Western blotting and determined that enzyme PDH45 was located in the nucleus and cytosol. Biochemical analyses of recombinant PDH45 shown that the optimum concentration of ATP for DNA unwinding activity was found to be 0.6 mM and ATP was the best cofactor utilized by the PDH45 while dATP supported 87% of activity. The kinetics of the unwinding reaction of enzyme PDH45 at optimum assay conditions showed a linear increasing rate up to 45 minutes. Titration of unwinding activity with increasing amount of purified PDH45 showed a saturation beyond 40 ng. The enzyme had no specific preference for tailed fork structures of the substrates. However, if the duplex region of the substrate increased to 34 bps in tailless substrate or 41 bp in tailed substrate, the PDH45 failed to unwind. To determine the direction of translocation of the PDH45, two substrates, one specific for 3’ to 5’ direction and other for 5’ to 3’ direction were constructed. The results showed that enzyme PDH45 contained 3’ to 5’ direction unwinding activity and not the 5’ to 3’ direction activity. Our data is in supporting that the PDH45 is an important multifunctional protein involved in DNA and RNA metabolism, in the regulation of protein synthesis and in maintaining the basic activities of the cell.